The Correlation between Students’ Mastery of Adverbs and Their Writing Ability of Recount Text - Rochmawan, Muhammad Rizky (Journal of Educational Review and Cultural Studies, 2023)
This study aimed to examine the relationship between students' mastery of adverbs and their success in producing recount texts. It also examined how well the students could use adverbs in their writing. This study's methodology combined a correlational approach with pre-experimental techniques. The findings demonstrated that students had an excellent grasp of adverbs, as seen by the mean value of their scores as well as their writing scores on the pre- and post-tests. The post-test revealed a constant increase in their score. The substantial association between the two variables was caused by the fact that the r-value was higher than the r product moment's critical value. Students' success in producing recount texts and their command of adverbs were significantly positively correlated. As a result, the better the students' writing recount text, the higher their adverb mastery score will be. The determination coefficient (r2) that was obtained indicated that 41.5% of the variation in writing performance may be attributed to the students' adverb competence. This demonstrated that the mastery of adverbs by students can account for both increases and decreases in writing scores by up to 41.5% through a linear relationship using the regression equation = 49.148 + 0.417X. In other words, the students' proficiency with adverbs had a significant influence on their success in writing recounts, with a proportion of 41.5%, leaving the remaining 58.5% to other considerations.